Compost Quality of Nyamplung (Calophyllum inophyllum L.) Solid Waste Oil Industri with Four Starters - Eritrina Windyarini; Budi Leksono; Tri Maria Hasna (Jurnal Wasian, 2018)
The purpose of this research is to utilized and provide added value from dregs seed of nyamplung solid waste through composting process using several starters, and findout the compost chemical character. The research was design as randomized complete (CRD) with 4 types of starters as treatments (biostarter of cattle rumen contents, Prouponic Gb # 1, EM4, Primadec C-15) each with 3 replications. Analysis of 7 chemical properties parameters carried out on nyamplung dregs seed before and after the treatment included: pH, DHL, organic C, total N, C / N ratio, Total P, and total K by comparing to SNI No.19- 7030-2004. The results showed that DHL, C / N ratio, total N, P, and total K of dregs seed compost fulfilled the SNI. The type of starter treatments significantly affected the quality of nyamplung dregs seed compost (DHL, total N, P, and K levels). Types of starters showing the best results were Prouponic Gb # 1 and EM4 compared to other biostarters. Therefore, Prouponic Gb # 1 and EM4 were reccomended to be applied to process nyamplung dregs seed waste into high quality compost.Keywords: biostarter, dregs seed, compost, solid waste, nyamplung